Children consider self-interest in their decisions to help and share with victims of a third-party moral transgression - Tan, Wendi Hui Min (Nanyang Technological University, 2020)
The present study examined how cost and familiarity interact to influence the helping behaviors of 5- to 6-year-olds (N = 120) in a third-party moral transgression. We also investigated children’s sharing behaviors and moral evaluations towards the transgressor and victim of the transgression. Children were randomly assigned to one of four conditions, such that they had prior interaction with the victim (Familiarity), or none (No Familiarity); and were promised a sticker reward contingent on their timely completion of a coloring task (Cost), or awarded the stickers unconditionally (No Cost). After observing the transgressor destroy the victim’s block tower, children were assessed on their responses to the victim’s prompts for help, their willingness to share resources with the agents, and ratings of the agents’ moral goodness. Results showed that children were more likely to help a familiar than unfamiliar victim, but only when helping was non-costly. Moreover, in general, children were unlikely to offer instrumental help to the victim, except when helping was non-costly and the victim was a familiar person. While children shared resources more generously with the victim than transgressor, they were also generally selfish in their sharing, and kept more resources for themselves regardless of the recipient. Lastly, children evaluated the victim positively and the transgressor negatively in terms of moral goodness, thus showing a good understanding of the moral scenario. Taken together, our findings suggest that children’s decisions on whether to help and share with the victim of a moral transgression were largely influenced by self-interest.